Periodotopy in the gerbil inferior colliculus: local clustering rather than a gradient map - Schnupp, Jan W. H.; Garcia-Lazaro, Jose A.; Lesica, Nicholas A. (Frontiers in Neural Circuits, 2015)
Periodicities in sound waveforms are widespread, and shape important perceptual attributes of sound including rhythm and pitch. Previous studies have indicated that, in the inferior colliculus, a key processing stage in the auditory midbrain, neurons tuned to different periodicities might be arranged along a periodotopic axis which runs approximately orthogonal to the tonotopic axis. Here we map out the topography of frequency and periodicity tuning in the inferior colliculus of gerbils in unprecedented detail, using pure tones and different periodic sounds, including click trains, sinusoidally amplitude modulated noise and iterated rippled noise. We found the tonotopic map exhibited a clear and highly reproducible gradient across all animals, periodotopic maps varied greatly across different types of periodic sound and from animal to animal. Furthermore, periodotopic gradients typically explained only about 10% in the variance in modulation tuning between recording sites. However, there was a strong local clustering of periodicity tuning at a spatial scale of ca 0.5 mm, which also differed from animal to animal.